Macrophage-Colony Stimulating Factor Derived from Injured Primary Afferent Induces Proliferation of Spinal Microglia and Neuropathic Pain in Rats. - Masamichi Okubo (PLoS ONE, 2016)
Peripheral nerve injury induces proliferation of microglia in the spinal cord, which can contribute to neuropathic pain conditions. However, candidate molecules for proliferation of spinal microglia after injury in rats remain unclear. We focused on the colony-stimulating factors (CSFs) and interleukin-34 (IL-34) that are involved in the proliferation of the mononuclear phagocyte lineage. We examined the expression of mRNAs for macrophage-CSF (M-CSF), granulocyte macrophage-CSF (GM-CSF), granulocyte-CSF (G-CSF) and IL-34 in the dorsal root ganglion (DRG) and spinal cord after spared nerve injury (SNI) in rats. RT-PCR and in situ hybridization revealed that M-CSF and IL-34, but not GM- or G-CSF, mRNAs were constitutively expressed in the DRG, and M-CSF robustly increased in injured-DRG neurons. M-CSF receptor mRNA was expressed in naive rats and increased in spinal microglia following SNI. Intrathecal injection of M-CSF receptor inhibitor partially but significantly reversed the proliferation of spinal microglia and in early phase of neuropathic pain induced by SNI. Furthermore, intrathecal injection of recombinant M-CSF induced microglial proliferation and mechanical allodynia. Here, we demonstrate that M-CSF is a candidate molecule derived from primary afferents that induces proliferation of microglia in the spinal cord and leads to induction of neuropathic pain after peripheral nerve injury in rats.